Identification of a novel aminoglycoside O-nucleotidyltransferase AadA33 in Providencia vermicola - Feng, Chunlin; Gao, Mengdi; Jiang, Weiyan; Shi, Weina; Li, Anqi; Liu, Shuang; Zhang, Lei; Zhang, Xueya; Li, Qiaoling; Lin, Hailong; Lu, Junwan; Li, Kewei; et al. (Frontiers in Microbiology, 2022)
A novel chromosome-encoded aminoglycoside O-nucleotidyltransferase AadA33 was identified in Providencia vermicola strain P13. The AadA33 shares the highest amino acid identity of 51.28% with the function characterized AadA31. Antibiotic susceptibility testing and enzyme kinetics analysis revealed that the function of AadA33 is to mediate spectinomycin and streptomycin resistance. The recombinant strain harboring aadA33(pUCP20-aadA33/E. coli DH5α) displayed >256- and 128- fold increases in the minimum inhibitory concentration levels to spectinomycin and streptomycin, respectively, compared with the control strains pUCP20/DH5α. Enzyme kinetic parameters manifested the substrate of AadA33 including spectinomycin and streptomycin, with kcat/Km of 3.28×104 (M−1·s −1) and 3.37×104 (M−1·s −1), respectively. Bioinformatics analysis revealed its structural mechanism of antimicrobial resistance, genetic context, and phylogenetic relationship with other aminoglycoside O-nucleotidyltransferases. This study of AadA33 contributed to understanding the function and resistance mechanism of aminoglycoside O-nucleotidyltransferase.